Pengaruh Media Pembelajaran Berbasis Online Terhadap Motivasi Belajar Siswa Kelas X Di SMKN 7 Jakarta - Siti Nurjannah; Nadiah Nadiah (Departement of Mathematics Education, 2024)
The circumstances in the educational setting are what spurred this investigation where there is still minimal use of online-based learning media, as well as teaching staff who have not yet mastered the use of this media. This causes learning in class to become less interactive and boring, thereby reducing students' learning motivation. To address this issue, the suggested remedy is the use of online-based learning media, one of which is Google Form media. The goal of this study is to assess and collect trustworthy data about how online learning resources affect the motivation of SMK Negeri 7 Jakarta's class X Graphic Engineering students to learn. A sample of 43 respondents was selected using a straightforward random sampling methodology from a population of 287 students for this quantitative study. Forms of documentation, questionnaires, and observation were used to gather data. The method of data analysis makes use of product moment correlation. The product moment correlation coefficient, or